(untitled) (Research, Society and Development, 2022)
This study deals with the use of information and communication technologies (ICTs) in the routines of teachers of classes in the 2nd year of initial grades of Elementary School in the Municipality of Fortaleza. Its objectives are to evaluate the use of Google tools to automate the production of learning reports in the mentioned classes; demonstrate the evaluation process in the 2nd year classes of the initial years in the schools of the Municipality of Fortaleza; describe Google tools that enable the automation of the evaluation process; and to identify educators’ perceptions about the use of technology in this assessment routine. For that, a qualitative research was used as a methodology through bibliographical consultation between books and scientific articles that promote reflection on themes related to information and communication technologies, learning evaluation and pedagogical practice, and also an action research with professional educators from three municipal schools to collect their impressions on carrying out work routines, the evaluation process, from a manual and digital perspective. The results point to the perception that, in the automatic system for producing learning reports, the execution of this routine occurs quickly and efficiently, proving the relevance of ICTs for facilitating pedagogical practice.